Neuroprotective Effects of the Lithium Salt of a Novel JNK Inhibitor in an Animal Model of Cerebral Ischemia-Reperfusion - Schepetkin (Shchepyotkin) I. A. Igor Aleksandrovich; Shernysheva G. A. Galina Anatoljevna; Aliev O. I. Oleg Ibragimovich; Kirpotina L. N. Liliya Nikolaevna; Smol’iakova V. I. Vera Ivanovna; Osipenko A. N. Anton Nikolaevich; Plotnikov M. B. Mark Borisovich; Kovrizhina A. R. Anastasia Ruslanovna; Khlebnikov A. I. Andrey Ivanovich; Plotnikov E. V. Evgeny Vladimirovich; Quinn M. T. Mark (2022, 2022)
Title screen